(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Social media platforms are expanding globally to facilitate an infinite interchange of diverse content. They can be used as practical, all-purpose information and communication instruments by businesses, scientific communities, patient advocacy groups, and groups with particular interests because of their brief form and accessibility. Due to widespread internet connectivity, people may now obtain nutrition-related information almost anywhere. However, the quality and supplier knowledge of the accessible data varies. It is critical to comprehend how the public seeks information to give practical nutritional recommendations. Although it has been demonstrated that social media and the internet are becoming more popular places to find nutrition-related details, more information must be found about the individuals supplying it. There are also knowledge gaps about the people the public prefers to access online and how they utilize the knowledge they discover. To stay competitive in this quickly changing field, nutrition experts must recognize and comprehend how the information-seeking environment is changing rapidly to deliver current advice that appeals to the public. It is imperative to safeguard against false information and advance nutrition in the digital era by skillfully disseminating public health information supported by evidence. This investigation aims to determine if social media can provide trustworthy information and knowledge regarding dietetics and nutrition. This study uses user-generated content on Twitter to find themes related to a healthy diet and to ascertain users’ opinions on different food styles.